E-wom’s Role in Driving Purchase Intention during Covid-19 Pandemic - Immanuel, Dewi Mustikasari; Merlin, Mariana (Jurnal Bisnis dan Manajemen, 2022)
Testimonials are one of the marketing tools that can have a big impact on consumers. Testimony is a form of electronic word of mouth (E-wom) where the information contained in E-wom will be very important as a reference for consumers when they want to make a purchase of a product. This research aims to find out the influence of E-wom quality, E-wom quantity, and E-wom credibility on the purchase intention of fashion products on the online marketplace. The population in this study are people who have visited marketplaces such as tokopedia, shopee, and bukalapak in Surabaya. The sampling method used is purposive sampling, with the number of samples being 385 respondents. Respondent data is collected by distributing questionnaires online. This study used multiple linear regression analysis in SPSS 22 as an analysis tool. The findings of this analysis show that E-wom quality affects purchase intention, E-wom quantity affects purchase intention, and E-wom credibility affects purchase intention. Â